Perimembranous ventricular septal defect following His bundle lead implantation. (9th June 2020) - De Pooter, Jan; Calle, Simon; Bove, Thierry; Van Heuverswyn, Frédéric E.; Timmermans, Frank
Abstract: His bundle pacing (HBP) offers physiologic pacing by placing the pacing lead directly to the His bundle. We present a case in which a HBP lead, implanted at the fragile membranous septum, resulted in a persistent restrictive perimembranous ventricular septal defect (VSD). This complication of HBP has not been reported before but brings new insights in the discussion regarding the optimal position of a pacing lead in the ventricular septum. The fragility of the membranous septum and low rate of spontaneous closure of membranous VSD, might favor lead placement in the muscular septum when aiming for physiologic pacing.